Re: Effects of Abstinence Self-Efficacy and Outcome Expectancies of Tobacco Smoking on the Desire to Quit Among Saudi Women: A Cross-Sectional Mediation Analysis. (21st June 2022) - Regmi, Sanjaya; Ward, Kenneth D
This letter offers commentary on Alanazi and colleagues recent analysis of desire to quit tobacco use among Saudi women, and suggestions for future studies.